Disaster Communication dalam Mitigasi Penanggulangan Banjir - Arzuri, Musvita Rahma; Zulfiningrum, Rahmawati (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Floods are one of the disasters that often occur in Indonesia, especially in the city of Semarang, when entering the rainy season, and cause various impacts on the community. This study aims to analyze disaster communication in flood disasters in Tlogosari Kulon Semarang. Effective communication between the Semarang City Regional Disaster Management Agency (BPBD) and the community is needed, especially in flood disaster management. This study uses disaster communication theory, a phenomenological approach, and qualitative methods by conducting in-depth interviews, observations, and documentation. The study results show that BPBD utilizes an internal communication system through a data and information center, a strap system, or the current situation in responding to disasters to find out conditions at the flood disaster location and map the impacts caused. Disaster communication carried out by the Semarang City BPBD in flood management includes: 1) pre-disaster is carried out by socializing flood management through social media accounts, 2) disaster response management in flood disaster management through two-way communication with the Meteorology, Climatology, and Geophysics Agency (BMKG) and the River Area Large Hall (BBWS), and, 3) post-disaster by recovering from the impact of flood disasters through collaboration and evaluation activities. The use of digital communication channels plays an important role in the dissemination of information to improve preparedness and rapid response during disasters. Mitigation in flood management and disaster recovery processes requires active community participation in every stage